Kajian Strategi Manajemen Kesiswaan untuk Meningkatkan Kualitas Pendidikan di Sekolah Menengah Kejuruan - Angela Yosiana; Ernawati Ernawati; Jonni Mardiza (Journal on Education, 2024)
This study aims to examine effective student management strategies in improving the quality of education in Vocational High Schools (SMK). Student management plays an important role in creating a conducive educational environment, which has a direct impact on students' academic success and character development. Through the Systematic Literature Review (SLR) approach, this study collects and analyzes previous studies that discuss the relationship between student management and the quality of education in SMK. The results of the study indicate that student management strategies, such as managing extracurricular activities, character building, and student supervision and motivation, can significantly improve the quality of education in SMK. This study provides insights for SMK managers and policy makers to optimize student management in order to create higher quality education that is relevant to industry needs.